Thermo-oxidative degradation of graphite/epoxy composite laminates: Modeling and long-term predictions (eXPRESS Polymer Letters)
Thermo-oxidative degradation of graphite/epoxy composite laminates due to exposure to elevated temperatures was characterized using weight loss and short beam strength (SBS) reduction data. Test specimens obtained from 24-ply, unidirectional AS4/3501-6 graphite/epoxy laminates were subjected to 100, 150, 175, and 200°C for 5000 hours (208 days) in air. Predictive differential models for the weight loss and short beam strength reduction were developed using the isothermal degradation data only up to 2000 hours. Then, the predictive capabilities of both models were demonstrated using the longer term, 5000 hours degradation data. The proposed models were first order differential expressions that can be used to predict degradation in an arbitrary, time-dependent temperature environment. Both models were able to estimate the actual degradation levels accurately. In particular, excellent agreement was obtained when the degradation temperature was lower than 200°C.